2022
DOI: 10.1093/ckj/sfac092
|View full text |Cite
|
Sign up to set email alerts
|

Novel somatic PBX1 mosaicism likely masking syndromic CAKUT in an adult with bilateral kidney hypoplasia

Abstract: Background Congenital abnormalities of the kidney and urinary tract (CAKUT) are characterized by vast phenotypic heterogeneity and incomplete penetrance. Although CAKUT represent the main cause of pediatric chronic kidney disease, only around 20% can be explained by single-gene disorders to date. While pathogenic alterations of PBX1 were recently associated with a severe form of syndromic CAKUT, most CAKUT-patients survive childhood and adolescence to reach end-stage kidney disease later in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Renal agenesis, hyperechogenicity, pelvicalyceal dilation, bilateral nephroureters, ectopic kidneys, horseshoe-shaped kidneys, bilateral vesicoureteral reflux, and small urethral valves are common PBX1 mutant renal phenotypes, though renal agenesis is rarer. In the study by Petzold et al (2022), chronic kidney disease stage 3 was observed at the time of the onset except in two adult patients with bilateral renal hypoplasia. Most patients were younger than 5 years of age at the time of their first diagnosis, and their renal functions declined variably.…”
Section: Pbx1 In Renal Developmentmentioning
confidence: 90%
“…Renal agenesis, hyperechogenicity, pelvicalyceal dilation, bilateral nephroureters, ectopic kidneys, horseshoe-shaped kidneys, bilateral vesicoureteral reflux, and small urethral valves are common PBX1 mutant renal phenotypes, though renal agenesis is rarer. In the study by Petzold et al (2022), chronic kidney disease stage 3 was observed at the time of the onset except in two adult patients with bilateral renal hypoplasia. Most patients were younger than 5 years of age at the time of their first diagnosis, and their renal functions declined variably.…”
Section: Pbx1 In Renal Developmentmentioning
confidence: 90%